The Effect of Emotion Regulation on The Aggressiveness of Adolescent Online Game User During The Covid-19 Pandemic - Itsna Putri Nur Hanifa (Bisma The Journal of Counseling, 2022)
This study aims to determine the effect of emotion regulation on the aggressiveness of adolescent online game users during the COVID-19 pandemic. This research uses descriptive quantitative method. The population in this study were all students of SMP N 5 Temanggung and SMP N 1 Kedu totaling 479 respondents, then for the sample taken as many as 128 respondents with non-probability sampling technique. The data analysis technique used multiple linear regression test technique. The results of this study show the effect of emotion regulation on the aggressiveness of online game users during the covid-19 pandemic, this is shown by the results of the partial significance test / t test with the results of 0.005 < 0.05 and the t value of-2.884 which means that "emotional regulation has an effect on negative on aggressiveness and if the emotional regulation of online game users increases, the aggressiveness of online game users will also decrease. So if the emotion regulation of teenagers who use online games is high or can manage their emotions well, it will reduce the level of aggressiveness of teenagers who use online games. Counseling service programs that can be provided to students are related to increasing emotional regulation in adolescents.